RELEVANSI NILAI SELISIH LOANS BOOK VALUE DAN LOANS FAIR VALUE, BOOK VALUE PER SHARE, DAN EARNINGS PER SHARE TERHADAP HARGA SAHAM PERUSAHAAN PERBANKAN DI INDONESIA - Rizka Amalia Utami; Pipin Fitriasari (STIE Madani Balikpapan, 2020)
The goal of this research is to analyze the effect of the difference of loans book value andloans fair value, book value per share, and earnings per share to stock price on banks inIndonesia. The objects are 29 conventional banks which are listed in Indonesia StockExchange during 2015-2018 with 116 samples. The data used in this research is secondarydata obtained from Indonesia Stock Exchange (www. idx.co.id). The hypothesis testingmethod are multiple linear regression analysis techniques using SPSS (Statistical Productand Service Solutions) application. After testing, the final results of the study showed thatthe difference between the loan book value and loans fair value with a significance value(sig. 0.760> 0.05) had no effect on stock prices, earnings per share with a significance value(sig. 0.166> 0.05) no effect on stock prices, while for the variable book value per share witha significance value (sig. 0,000 <0.05) affect the stock price.